TiNb2O7 nano-particle decorated carbon cloth as flexible self-support anode material in lithium-ion batteries. (1st February 2020) - Luo, Jing; Peng, Jiao; Zeng, Peng; Wu, Zhenyu; Li, JinYe; Li, Wangwu; Huang, Yuehua; Chang, Baobao; Wang, Xianyou
Abstract: The activated carbon cloth (ACC@TNO) with flexible self-support structure, which is decorated by TiNb2 O7 (TNO) nanoparticle, is successfully obtained through hydrothermal reaction and calcination process in high temperature, and is used as the binder-free anode material of lithium ion batteries (LIBs). The morphology characteristic, pore structure properties and the phase structure of the ACC@TNO composites are detailedly studied by the scanning electron microscopy (SEM), Brunauer–Emmett–Teller adsorption/desorption measurement (BET) and X-ray diffraction (XRD). Meanwhile, the electrochemical properties of ACC@TNO composite are further tested by cyclic voltammetry and galvanostatic charge-discharge tests. As a result, the LIBs with ACC@TNO as anode material shows an initial discharge capacity of 356 mAh g −1 and an initial coulombic efficiency (ICE) of 87% at the current density of 0.5 C with the voltage window of 1.0–3.0 V. It also has been found that the reversible capacity can still keep as 290 mAh g −1 with the capacity retention of 81% after 500 cycles. Besides, when the cutoff voltage range is set to 0.01–3.0 V, the reversible capacity can reach 340 mAh g −1 . Apparently, this work is of great significance for the exploration of the new anode materials with high performance and long cyclic life in next-generation LIBs. Graphical abstract: Image 1 Highlights: The ACC@TNO composite is obtained by epitaxially growing TNO particles on ACC surface like stab grown on the thorn. The thiourea is use as a nitrogen source and sulfur source to treat the carbon cloth. The ACC@TNO composite is binder-free anode material. The ACC@TNO composite displays good electrochemical performance.